Rule of law & property rights, FDI, and environmental quality nexus: a dynamic panel threshold analysis - Imam, Muhammad Asim; Azman-Saini, W. N.W.; Abbas, Muhammad Adeel (Springer Nature, 2025)
The present study thoroughly examines the relationship between foreign direct investment (FDI), the rule of law, and environmental quality. This research uses a threshold method covering 123-panel countries from 2000 to 2019. The current study is distinctive given that it employs a new methodology and examines the nonlinear relationship between environmental quality and FDI inflows and the moderating factors that influence this relationship. An inverted U-shaped curve is identified, and the EKC hypothesis is verified through the conducted analysis. Current results imply that even though FDI accompanies higher levels of 2, its effect can become beneficial based on the institution’s quality. The existing study contributes to previous research because it provides new insights into the ability of FDI to ensure environmental sustainability. Current findings indicate a need for strong legal institutions to make FDI environmentally friendly and facilitate global agendas to achieve carbon neutrality.